Chemical and Biological insights of Ouratea hexasperma (A. St.-Hil.) Baill.: a source of bioactive compounds with multifunctional properties. Issue 10 (19th May 2019) - Fidelis, Queli Cristina; Faraone, Immacolata; Russo, Daniela; Aragão Catunda-Jr, Francisco Eduardo; Vignola, Lisiana; de Carvalho, Mario Geraldo; de Tommasi, Nunziatina; Milella, Luigi
Abstract: The study aimed to evaluate in vitro antioxidant, anticholinesterase and antidiabetic properties of Ouratea hexasperma (A. St.-Hil.) Baill. The inflorescence methanol extract and the ethyl acetate fraction of leaves and stems reported the highest Relative Antioxidant Capacity Index (RACI), whereas the dichloromethane fraction of leaves was the best inhibitor of α -amylase and α -glucosidase. T rans -3- O -methyl-resveratrol-2- C - β -glucoside, lithospermoside, 2, 5-dimethoxy- p -benzoquinone, lup-20(30)-ene-3β, 28-diol, 7- O -methylgenistein, apigenin and luteolin and amentoflavone were isolated from O. hexasperma . Resveratrol derivative was isolated for the first time in Ochnaceae family. Luteolin, followed by apigenin, reported the highest Relative Antioxidant Capacity Index and they were also the best inhibitors of α-glucosidase enzyme. Abstract :